Efeito do selante de fibrina BthTL combinado ao peptídeo de ação mimética ao TNF na regeneração nervosa periférica - Oliveira, Tárika Gonçalves do Carmo (2019)
Surgical intervention is necessary whenever peripheral nerve laceration occurs. Using tubular prostheses that guide and protect injury area and the possibility of inserting, within this prosthesis, drugs and molecules that act positively in nerve regeneration is a perspective in the current clinics and can serve as an alternative for standard tools of nerve repair. Our aim was to investigate the effect of BthTL fibrin sealant, associated or not to a synthetic TNF mimetic peptide, on axonal regeneration and functional recovery of sciatic nerve after neurotmese. For this purpose, Wistar rats were submitted to left sciatic nerve neurotmese and subsequent tubulization surgery. Three groups were formed: empty tube, tube+glue group (filled with fibrin sealant), and tube+glue+pep group (filled with sealant mixed with TNF mimetic peptide). Animals were analyzed for sensory and motor function over 45 days. At the end of this period, animals were euthanized and nerves were collected for immunostaining (neurofilament, GAP43, S100-β, NGFRp75 and Iba-1) and for transmission and light electron microscopy in order to count myelinated, unmyelinated and degenerated fibers, as well as for evaluation of the morphometric analysis of regenerated fibers (diameter of myelin fibers, diameter of myelin axons, thickness of myelin sheath and g ratio). Histopathological analysis and collagen staining were also performed. Our data did not show motor or sensory functional recovery. Intense inflammatory infiltrate with a higher Iba-1 expression and increased NGFRp75 receptor, which characterizes Schwann cell regenerative phenotype, was seen in the presence of the BthTL sealant associated to peptide. In addition, this group had higher myelin thickness and fiber diameter and more type III collagen. Nerves extracted from sealant tubes showed intermediate results between empty tube and tube+glue+pep for NGFRp75, inflammation and collagen; on fiber counts, these nerves showed more degenerate fibers and fewer unmyelinated axons than any group. Empty tube group showed superiority only in GAP43 expression. Altogether, our data suggest that the sealant associated to TNF mimetic peptide induced greater local inflammation influencing the Schwann cells in order to act positively in the process of peripheral nerve regeneration.